The Good, the Bad, and the Ugly: An Autoethnographic Journey on Doing Participatory Action Research as a Graduate Student. (April 2018) - Lac, Van T.; Fine, Michelle
The lead author documents the promises and pitfalls of doing critical participatory action research (PAR) as a graduate student within traditional institutions. This autoethnographic essay captures the vulnerabilities of the first author as she reflects on the human work that draws her to PAR, details the tensions that surfaced in the daily practices of doing PAR with youth, and addresses unforeseen hurdles that emerged from the ethics review board and the university–school partnership. The piece concludes with an epilogue from Dr. Michelle Fine, a senior scholar in the field of critical PAR, as she responds to the concerns raised in this essay.